Cirsoid Aneurysm of the Scalp - Faran Ahmad (Romanian Neurosurgery, 2017)
Cirsoid aneurysms (arteriovenous malformations [AVMs]) are Anomalous fistulous arteriovenous communications of scalp with ill-defined natural course that are rarely encountered in neurosurgery. Patients with AVM of the scalp present clinically with headache and either a small innocuous-looking subcutaneous scalp lump or a large, pulsatile mass with or without bruit, which has a propensity to massive hemorrhage. Complex vascular anatomy and interconnections and high shunt flow make their management difficult. We report a rare case of a 40-year-old man who presented with a swelling over his occipital region that progressively enlarged over the course of 6 years. Being high flow shunt surgical excision was attempted.